Contrasting pattern of allelic variation in heat shock factor-1 (HSF-1), a major candidate gene regulating heat stress response across Indian native (Bos indicus), crossbred and exotic (Bos taurus) cattle - Amandeep Jast; Monika Sodhi; Rakesh Ranjan; Preeti Verma; Nampher Mashering; Prince Vivek; Manish Tiwari; Parvesh Kumari; Manishi Mukesh (Journal of Livestock Biodiversity, 2025)
The aim of this study was to assess the frequency distribution of selected SNPs in heat shock factor-1 (HSF-1) gene across indigenous, exotic and crossbred cattle. For this study, a total of 1594 genomic DNA samples of 15 Indian native cattle breeds; 2 exotic (Holstein Friesian and Jersey); and 1 crossbred cattle (Karan Fries) were screened for 2 SNPs at locus 909 in intron 3 and locus 4693 in 3’-UTR. The digestion of 129bp product corresponding to 909 locus revealed 3 different genotypes CC (129bp), TC (129bp, 88bp and 41bp) and TT (88bp and 41bp). The allele C was predominant in all the native cattle with frequency of 0.935, whereas the frequency of allele C in Holstein Friesian (HF) and Karan Fries (KF) was 0.463 and 0.503 respectively. The restriction digestion of 287bp amplicon corresponding to 4693 locus revealed 3 different genotypes GG (178bp, 61bp, 41bp and 7bp), GT (178bp, 68bp, 61bp, 41bp and 7bp) and TT (178bp, 68bp and 41bp). The allele T was predominant in all indigenous cattle and Jersey with frequency of 0.744 and 0.643, respectively. However, in HF and KF cattle, allele G was predominant with frequency 0.563 and 0.545, respectively. The data suggested sequence variability in HSF-1 gene and such genetic variation might be playing crucial role during heat stress response in diferent cattle populations.